Glass-ceramics, method for preparing glass-ceramics, and electronic equipment

By introducing Nb2O5 into the microcrystalline glass and forming crystal phases of cherry and niobate, the excessive growth of the phosphate crystal phase is suppressed, and the problem of poor mechanical properties of the microcrystalline glass is solved, and the improvement of high hardness and drop resistance is achieved. It is suitable for on the electronic device panel and back panel.

CN114426398BActive Publication Date: 2025-01-17HUAWEI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011178343.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-29
Publication Date
2025-01-17
Estimated Expiration
2040-10-29

AI Technical Summary

Technical Problem

The excessive growth or uneven growth of the phosphate crystal phase during the cooling process of existing microcrystalline glasses leads to poor mechanical properties, which is difficult to meet the high hardness and drop resistance requirements of the panels and back plates of mobile terminal equipment.

Method used

By introducing Nb2O5 and controlling its ratio to P2O5, excessive growth or uneven growth of the phosphate crystal phase is inhibited, and the cymbic crystal phase and niobate crystal phase are formed during the microcrystalization process, forming a surface compressive stress layer. Improve mechanical properties.

Benefits of technology

It effectively improves the mechanical properties of microcrystalline glass, enhances its compressive stress resistance and transparency, and is suitable for high-performance electronic equipment panels and back panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114426398B_ABST
    Figure CN114426398B_ABST
Patent Text Reader

Abstract

The present application provides a glass-ceramic, a method for preparing the glass-ceramic, and an electronic device. The glass-ceramic includes: a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase. The present application utilizes the competitive growth of the niobate crystal phase and the phosphate crystal phase during the microcrystallization process to effectively inhibit the excessive growth or uneven growth of the phosphate crystal phase, thereby improving the mechanical properties of the glass-ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and more specifically, to a glass-ceramic, a method for preparing the glass-ceramic, and an electronic device. Background Art

[0002] With the widespread and frequent use of mobile devices such as mobile phones, the performance requirements for the panels and backplanes of cover products are getting higher and higher, such as higher hardness, higher strength, and better drop resistance. Since microcrystalline glass has higher body strength than ordinary glass, the use of microcrystalline glass to prepare the panels and backplanes of cover products has become more and more popular.

[0003] In the preparation of existing microcrystalline glass, P2O5 is usually used as a nucleating agent to promote the nucleation and crystallization of the matrix glass. Although P2O5 can effectively form nuclei and induce crystallization, due to the extremely fast growth rate of the phosphate crystal phase, it is easy to overgrow or grow unevenly during the cooling process of the microcrystalline glass, which will lead to the deterioration of the macroscopic mechanical properties of the final microcrystalline glass product.

[0004] Therefore, how to improve the mechanical properties of glass-ceramics is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The present application provides a glass-ceramic, a method for preparing the glass-ceramic, and an electronic device, which can improve the mechanical properties of the glass-ceramic.

[0006] In a first aspect, a microcrystalline glass is provided, comprising: a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase.

[0007] It should be understood that the niobate crystal phase is a microcrystalline phase, and its size is less than or equal to 80 nm.

[0008] The microcrystalline glass provided in the present application includes a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase. The competitive growth of the niobate crystal phase and the phosphate crystal phase during the microcrystalline process effectively inhibits the excessive growth or uneven growth of the phosphate crystal phase, thereby improving the mechanical properties of the microcrystalline glass.

[0009] In combination with the first aspect, in certain implementations of the first aspect, the chemical composition of the microcrystalline glass includes, by mole, a first component, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts; wherein the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

[0010] In the existing microcrystalline glass preparation process, P2O5 is usually used as a nucleating agent to promote the nucleation and crystallization of the matrix glass. Although P2O5 can effectively form nuclei and induce crystallization, due to the extremely fast growth rate of the phosphate crystal phase, it is easy to overgrow or grow unevenly during the cooling process of the microcrystalline glass, which will lead to the deterioration of the macroscopic mechanical properties of the final microcrystalline glass product.

[0011] Therefore, in the embodiments of the present application, by introducing Nb2O5 and adjusting the ratio of Nb2O5 to P2O5, the excessive growth or uneven growth of the phosphate crystal phase can be effectively inhibited, thereby improving the mechanical properties of the microcrystalline glass.

[0012] In combination with the first aspect, in certain implementations of the first aspect, the chemical composition of the microcrystalline glass also includes a second component, and the second component includes: at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

[0013] In combination with the first aspect, in certain implementations of the first aspect, the glass-ceramics includes a surface compressive stress layer, and the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

[0014] It should be understood that the surface compressive stress layer of the microcrystalline glass also includes: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0015] In combination with the first aspect, in certain implementations of the first aspect, the surface compressive stress of the surface compressive stress layer is greater than or equal to 200 MPa, and the depth of the surface compressive stress layer is greater than or equal to 15 μm.

[0016] In combination with the first aspect, in certain implementations of the first aspect, at least one of the nepheline crystal phase, the hexagonal potassium nepheline crystal phase, the phosphate crystal phase and the niobate crystal phase is a nanocrystalline phase, and a size of the nanocrystalline phase is less than or equal to 80 nm.

[0017] In combination with the first aspect, in certain implementations of the first aspect, the light transmittance of the microcrystalline glass in the visible light spectrum range is greater than or equal to 75%.

[0018] In combination with the first aspect, in certain implementations of the first aspect, the glass-ceramics is colorless or light-colored and transparent.

[0019] In combination with the first aspect, in certain implementations of the first aspect, the color coordinates of the microcrystalline glass in the CIE LAB color space are in the following range: L* is 80 to 100, a* is -20 to 5, and b* is -20 to 5.

[0020] In a second aspect, a method for preparing microcrystalline glass is provided, comprising: preparing a base glass; and heat-treating the base glass to obtain microcrystalline glass, wherein the microcrystalline glass comprises: a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase.

[0021] Optionally, the preparation process of the matrix glass may be as follows: firstly, a mixture of various raw materials is melted into glass liquid at high temperature, and then the glass liquid is cooled and formed into a flat plate or other shapes during the cooling process, namely, the matrix glass.

[0022] It should be understood that the chemical compositions of the above raw materials, base glass and glass-ceramics are the same.

[0023] Optionally, the forming method can be a float method, a calendaring method, an overflow method, a casting method, a roll pressing method, a molding method, etc.

[0024] Alternatively, the melting process may employ conventional electric melting or flame melting methods.

[0025] It should be understood that the niobate crystal phase is a microcrystalline phase, and its size is less than or equal to 80 nm.

[0026] In an embodiment of the present application, the base glass is heat treated to obtain a microcrystalline glass including a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase, wherein the competitive growth of the niobate crystal phase and the phosphate crystal phase during the microcrystallization process effectively inhibits the excessive growth or uneven growth of the phosphate crystal phase, thereby improving the mechanical properties of the microcrystalline glass.

[0027] In combination with the second aspect, in certain implementations of the second aspect, the chemical composition of the matrix glass includes, by mole, a first component, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts; wherein the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

[0028] In the existing microcrystalline glass preparation process, P2O5 is usually used as a nucleating agent to promote the nucleation and crystallization of the matrix glass. Although P2O5 can effectively form nuclei and induce crystallization, due to the extremely fast growth rate of the phosphate crystal phase, it is easy to overgrow or grow unevenly during the cooling process of the microcrystalline glass, which will lead to the deterioration of the macroscopic mechanical properties of the final microcrystalline glass product.

[0029] Therefore, in the embodiments of the present application, by introducing Nb2O5 and adjusting the ratio of Nb2O5 to P2O5, the excessive growth or uneven growth of the phosphate crystal phase can be effectively inhibited, thereby improving the mechanical properties of the microcrystalline glass.

[0030] In combination with the second aspect, in certain implementations of the second aspect, the chemical composition of the base glass also includes a second component, and the second component includes: at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

[0031] In combination with the second aspect, in certain implementations of the second aspect, the heat treatment of the base glass includes: heating the base glass to 600-850°C at a rate of 1-20°C / min and keeping it warm for 1-3 hours; or, heating the base glass to 550-750°C at a rate of 1-20°C / min and keeping it warm for 0.5-4 hours to complete nucleation, and then heating the nucleated base glass to 650-900°C and keeping it warm for 0.5-3 hours to complete crystallization.

[0032] In combination with the second aspect, in certain implementations of the second aspect, the method further includes: performing ion exchange treatment on the microcrystalline glass to obtain a surface compressive stress layer, wherein the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

[0033] Optionally, the surface compressive stress layer of the microcrystalline glass also includes: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0034] Optionally, the ion exchange method can be a one-step method, i.e. exchanging sodium ions on the surface of the microcrystalline glass with potassium ions; or it can be a two-step method, i.e. first exchanging lithium ions in the surface of the microcrystalline glass with sodium ions, and then exchanging sodium ions in the surface of the microcrystalline glass with potassium ions.

[0035] In an embodiment of the present application, the microcrystalline glass is subjected to ion exchange treatment so that a surface compressive stress layer is formed on the surface of the microcrystalline glass, so that the microcrystalline glass can withstand higher surface compressive stress, thereby further improving the mechanical properties of the microcrystalline glass.

[0036] In combination with the second aspect, in certain implementations of the second aspect, before the base glass is heat-treated, the method also includes: performing ion exchange treatment on the base glass so that the microcrystalline glass obtained after the base glass is heat-treated includes a surface compressive stress layer, and the surface compressive stress layer includes a hexagonal potassium nephrite crystal phase.

[0037] Optionally, the surface compressive stress layer of the microcrystalline glass also includes: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0038] Optionally, the ion exchange method can be a one-step method, i.e. exchanging sodium ions on the surface of the microcrystalline glass with potassium ions; or it can be a two-step method, i.e. first exchanging lithium ions in the surface of the microcrystalline glass with sodium ions, and then exchanging sodium ions in the surface of the microcrystalline glass with potassium ions.

[0039] In an embodiment of the present application, the base glass is subjected to ion exchange treatment so that the microcrystalline glass obtained after heat treatment of the base glass includes a surface compressive stress layer, so that the microcrystalline glass can withstand higher surface compressive stress, thereby further improving the mechanical properties of the microcrystalline glass.

[0040] In a third aspect, a glass-ceramic product is provided, wherein the glass-ceramic product is made of the glass-ceramic as described in the first aspect or any one of the implementations of the first aspect.

[0041] Optionally, the glass-ceramic product may be a housing in an electronic device or a glass cover plate above a display screen.

[0042] In a fourth aspect, an electronic device is provided, which includes a shell and a display screen, wherein the display screen is mounted on the shell, and the display screen includes a glass cover plate and a display module, wherein the glass cover plate is arranged on the display module; wherein the shell includes the microcrystalline glass as described in the first aspect or any one of the implementations of the first aspect; and / or the glass cover plate includes the microcrystalline glass as described in the first aspect or any one of the implementations of the first aspect.

[0043] It should be understood that the rear surface of the housing can also be referred to as the back plate of the electronic device, and the glass cover can be referred to as the panel of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 is an example diagram of ion exchange provided in an embodiment of the present application;

[0045] Figure 2 is an X-ray diffraction spectrum of a glass-ceramic provided in an embodiment of the present application;

[0046] Figure 3 is a structural example diagram of a glass-ceramic provided in an embodiment of the present application;

[0047] Figure 4 This is an example diagram of a method for preparing glass-ceramics provided in an embodiment of the present application;

[0048] Figure 5 is the X-ray diffraction spectrum of the glass-ceramics of the comparative example of the present application;

[0049] Figure 6 This is an example of the microscopic morphology of the glass-ceramics of the comparative example of the present application;

[0050] Figure 7 This is an example diagram of the microscopic morphology of a glass-ceramic provided in an embodiment of the present application;

[0051] Figure 8 This is another example of the microscopic morphology of glass-ceramics provided in an embodiment of the present application;

[0052] Fig. 9 It is an exemplary structural diagram of an electronic device provided in an embodiment of the present application. DETAILED DESCRIPTION

[0053] In order to facilitate understanding of the solutions of the embodiments of the present application, the concepts and related technologies involved in the present application are first described.

[0054] Glass-ceramics: also known as glass ceramics, is a material containing both crystalline and glass phases obtained by controlling the crystallization of the base glass during the manufacturing process. The glass base and the microcrystalline particles dispersed in it can be observed by scanning electron microscope (SEM) or transmission electron microscope (TEM). Glass-ceramics are generally opaque, but when the crystalline particles are smaller than the wavelength of visible light (for example, less than 300nm), it is possible to obtain transparent glass-ceramics. According to the crystalline phase of glass-ceramics, glass-ceramics can achieve higher fracture toughness than ordinary glass, thereby improving the mechanical properties of cover products.

[0055] Ion exchange treatment: Ion exchange treatment is a chemical strengthening method. Figure 1 As shown, the ion exchange treatment is to immerse the glass (microcrystalline glass or matrix glass) in a molten salt of alkali metals with larger ion radius (for example, a melt of sodium nitrate or potassium nitrate, etc.). At the glass transition temperature Tg of the glass, the large-radius alkali metal ions in the molten salt are exchanged with the small-radius alkali metals on the surface of the glass through ion exchange. The volume difference between the two after the ion exchange causes the glass surface to present a compressive stress state. Optionally, the ion exchange method can be a one-step method, that is, exchanging Na+ on the surface of the glass with K+; or it can be a two-step method, that is, first exchanging Li+ in the surface layer of the microcrystalline glass with Na+, and then exchanging Na+ in the surface layer of the microcrystalline glass with K+.

[0056] Surface compressive stress (CS): generally refers to the maximum compressive stress formed on the glass surface by chemically strengthened glass, which is used to protect the glass surface and inhibit surface defects from developing into cracks.

[0057] Depth of layer (DOL): generally refers to the depth of the strengthening ions used in chemically strengthened glass (such as potassium ions used to strengthen sodium glass) diffused into the glass. Generally speaking, the greater the depth of the compressive stress layer, the more helpful it is to improve the mechanical properties of the glass.

[0058] To facilitate understanding, the relevant background technology of the embodiments of the present application is briefly introduced.

[0059] With the widespread and frequent use of mobile terminal devices such as mobile phones, the performance requirements for the panels and backplanes of cover products are becoming higher and higher, such as higher hardness, higher strength, and better drop resistance. Since microcrystalline glass has higher body strength than ordinary glass, the use of microcrystalline glass to prepare the panels and backplanes of cover products has become more and more popular. Among the existing microcrystalline glass, nepheline microcrystalline glass containing Na+ has attracted widespread attention from researchers due to its excellent mechanical properties.

[0060] In the preparation of existing nepheline glass-ceramics, P2O5 is usually used as a nucleating agent to promote the nucleation of the matrix glass, and then undergoes appropriate crystallization heat treatment to obtain glass-ceramics with a mixed crystalline phase of nepheline and phosphate. Although P2O5 can effectively form nuclei and induce crystallization, due to the extremely fast growth rate of the phosphate crystal phase, it is easy to overgrow or grow unevenly during the cooling process of the glass-ceramics, which will lead to the deterioration of the mechanical properties and process performance of the glass-ceramics. It is mainly manifested in the natural cracking of the glass-ceramics during the cooling process after crystallization, or the cracking during cutting (after eliminating the influence of poor annealing), or the cracking during the chemical strengthening stage, or the glass-ceramics products are fragile during use.

[0061] In response to the above problems, the present application provides a microcrystalline glass, which can precipitate a niobate crystal phase during the crystallization process. Since the precipitation of the niobate crystal phase inhibits the excessive growth or uneven growth of the phosphate crystal phase, the mechanical properties of the microcrystalline glass can be improved.

[0062] The technical solution in this application will be described below in conjunction with the accompanying drawings.

[0063] It should be understood that the microcrystalline glass of the embodiments of the present application can be applied to electronic devices, for example, cover plates of electronic devices (for example, the front cover glass of a mobile phone screen, the rear cover (back plate) of a battery, etc.), shells, etc.

[0064] It should be understood that the microcrystalline glass of the embodiment of the present application can also be applied to other occasions, as long as there is a place in the occasion where microcrystalline glass with high mechanical properties is used, such as automotive use, and further such as car lamp covers, windshields, or dashboard glass in cars.

[0065] Figure 2 is an X-ray diffraction spectrum of a glass-ceramic provided in an embodiment of the present application. Figure 2 As shown, the glass-ceramics includes: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0066] It should be understood that Figure 2The X-ray diffraction spectrum of the microcrystalline glass shown is only used as an example, and the crystal phase composition of the microcrystalline glass in the embodiment of the present application is not limited thereto.

[0067] Optionally, in general, the microcrystalline glass may include the above three crystalline phases existing separately and also include a crystalline phase obtained by any combination of the above three. Exemplarily, the crystalline phase obtained by any combination of the above three may be: a crystalline phase obtained by combining any two of the above three; or: a crystalline phase obtained by combining the above three. It should be understood that the crystalline phase obtained by combination is a combined phase, which is different from the crystalline phase when the above three exist separately. It should also be understood that multiple combined crystalline phases obtained by any combination of the above three may exist in the microcrystalline glass at the same time, and the present application does not limit this.

[0068] Optionally, in actual operation, in addition to the above situation, some or all of the above three may not exist separately in the glass-ceramics, but exist in the form of a combined phase. For example, in special cases: the glass-ceramics may include a crystalline phase obtained by combining a nepheline crystal phase and a phosphate crystal phase, and a niobate crystal phase that is not combined with it; for another example, the glass-ceramics may include a crystalline phase obtained by combining a phosphate crystal phase and a niobate crystal phase, and a nepheline crystal phase that is not combined with it; for another example, the glass-ceramics may include a crystalline phase obtained by combining a nepheline crystal phase and a phosphate crystal phase, and a crystalline phase obtained by combining a nepheline crystal phase, a phosphate crystal phase and a niobate crystal phase. The specific composition is not limited in this application.

[0069] It should be understood that the above crystal phase composition is only used as an example and does not constitute a limitation of the present application. All obtained microcrystalline glass including the above combination falls within the protection scope of the present application.

[0070] Optionally, the above-mentioned glass-ceramics may also include a eucryptite crystal phase; and / or any combination of the eucryptite crystal phase and other crystal phases.

[0071] Optionally, the above-mentioned glass-ceramics may also include a hexagonal kalcylindrical phase; and / or any combination of a hexagonal kalcylindrical phase and other crystal phases.

[0072] For ease of description, in the following text, it is considered that the glass-ceramics includes: nepheline crystal phase, phosphate crystal phase and niobate crystal phase. However, it should be understood that the crystal phase composition of the actual glass-ceramics is not limited thereto.

[0073] Optionally, the chemical components of the microcrystalline glass include a first component, measured in molar parts, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts; wherein the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

[0074] In the embodiment of the present application, the chemical composition of the microcrystalline glass also includes Nb2O5, which effectively inhibits the excessive growth or uneven growth of the phosphate crystal phase during the microcrystallization process, thereby improving the mechanical properties of the microcrystalline glass.

[0075] Optionally, the chemical composition of the microcrystalline glass may further include a second component, the second component includes: at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

[0076] It should be understood that for the sake of ease of description, the example ratios of the above chemical components and the reasons why the chemical components can improve the mechanical properties of microcrystalline glass will be introduced in detail when the preparation method of microcrystalline glass is introduced below, and they will not be repeated here.

[0077] Optionally, the glass-ceramics may further include a surface compressive stress layer, wherein the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

[0078] Optionally, the surface compressive stress layer may also include: a nepheline crystal phase, a phosphate crystal phase and a niobate crystal phase.

[0079] For example, Figure 3 is a structural example diagram of a glass-ceramic provided in an embodiment of the present application. Figure 3 As shown, the microcrystalline glass 300 includes a surface compressive stress layer and an intermediate layer.

[0080] It should be understood that the surface compressive stress layer includes nepheline crystal phase, phosphate crystal phase, niobate crystal phase and hexagonal potassium nepheline crystal phase, and the intermediate layer includes nepheline crystal phase, phosphate crystal phase and niobate crystal phase.

[0081] It should be understood that the surface pressure layer may also include a crystalline phase obtained by any combination of the above four. For details, please refer to the above description and will not be repeated here.

[0082] Optionally, the surface compressive stress of the surface compressive stress layer is greater than or equal to 200 MPa. Preferably, the surface compressive stress of the microcrystalline glass is greater than or equal to 800 MPa.

[0083] Optionally, the depth of the surface compressive stress layer is greater than or equal to 15 μm. Preferably, the depth of the surface compressive stress layer is greater than or equal to 80 μm.

[0084] It should be understood that for the convenience of description, the preparation process of the surface compressive stress layer will be described in detail below and will not be repeated here.

[0085] Optionally, at least one of the nepheline crystal phase, the hexagonal potassium nepheline crystal phase, the phosphate crystal phase and the niobate crystal phase is a nanocrystalline phase, and a size of the nanocrystalline phase is less than or equal to 80 nm.

[0086] Optionally, the combined crystal phase obtained by any combination of the above four can also be a nanocrystalline phase, which is not limited in the present application.

[0087] It should be understood that the nanocrystalline phase refers to a crystalline phase having a size on the nanometer scale.

[0088] Optionally, the size of the nanocrystalline phase can be calculated by analyzing the X-ray diffraction pattern in combination with the Scherrer formula; the size can also be estimated by observing the microscopic morphology of the microcrystalline glass under a transmission electron microscope; it can also be calculated using the small-angle X-ray scattering method, which is not limited in this application.

[0089] Optionally, the light transmittance of the glass-ceramic in the visible light spectrum is greater than or equal to 75%. Preferably, the light transmittance is greater than or equal to 80%.

[0090] Optionally, the glass-ceramic is colorless or light-colored and transparent.

[0091] Optionally, the color coordinates of the glass-ceramics in the CIE LAB color space are in the following range: L* is 80 to 100, a* is -20 to 5, and b* is -20 to 5.

[0092] It should be understood that the size and light transmittance of the above-mentioned crystal phase can be achieved by adjusting the microcrystallization conditions or the raw material ratio, etc., and this application does not make any further limitations on this.

[0093] Figure 4 is an example diagram of a method for preparing microcrystalline glass provided in an embodiment of the present application. Figure 4 As shown, method 400 includes steps S410 and S420, which are described in detail below.

[0094] S410, preparing base glass.

[0095] Optionally, the chemical composition of the matrix glass includes a first component, measured in molar parts, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts; wherein the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

[0096] Optionally, the chemical composition of the matrix glass may further include a second component, the second component including at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

[0097] Optionally, the second component may also include a small amount of TiO2 and SnO2, and the application does not impose any specific limitation on the amount thereof.

[0098] The preparation process of the base glass is described in detail below.

[0099] The core process of the matrix glass manufacturing method of the embodiment of the present application is: batch material preparation → glass melting → cooling and molding, which is specifically described as follows.

[0100] 1) Preparation of batch materials: Prepare various raw materials according to the chemical composition of the base glass.

[0101] The chemical components of the matrix glass are exemplified below in conjunction with Table 1.

[0102] Table 1: (Unit: molar parts)

[0103]

[0104] Table 1 (continued):

[0105]

[0106] Table 1 (continued):

[0107]

[0108] Alternatively, the actual batch material may be formulated according to the above chemical composition; it may also be formulated using any materials, or oxides or other compounds, which when melted together with other batch material components will be converted into a matrix glass including the above chemical composition in appropriate proportions.

[0109] 2) Glass melting: A uniform mixture of batch materials is put into a melting furnace and melted at high temperature to obtain high-temperature molten glass, while removing bubbles and foreign matter in the molten glass.

[0110] Optionally, the melting process may adopt a conventional electric melting or flame melting method, which is not limited in the present application.

[0111] Optionally, the mixture of the batch materials may be pre-fired at 700-800° C. for 1-2 hours before melting the glass.

[0112] Optionally, the melting temperature may be 1400-1650° C. Optionally, during the melting process, the molten glass may be melted and refined at 1400-1650° C. for 8-16 hours.

[0113] 3) Cooling molding: During the cooling process of the glass liquid, the glass raw materials are made into plates or other shapes, that is, the matrix glass is prepared by using molding processes such as float method, calendering method, overflow method, casting method, rolling method, and molding method.

[0114] Optionally, after the formed base glass is obtained, it can be annealed at 550-700° C. for 6-12 hours to eliminate internal residual stress. It should be understood that in the embodiment of the present application, the prepared base glass is transparent, colorless and does not contain a crystalline phase.

[0115] S420, heat-treating the base glass to obtain glass-ceramics.

[0116] The obtained microcrystalline glass includes: nepheline crystal phase, phosphate crystal phase and niobate crystal phase.

[0117] It should be understood that the above heat treatment process is a microcrystallization process. Optionally, the microcrystallization process includes a one-step crystallization method and a two-step crystallization method. Specifically, the microcrystallization process includes: performing heat treatment at one or more pre-selected temperatures for the same or different times to produce one or more crystalline phases in the base glass, thereby achieving the purpose of microcrystallization.

[0118] Optionally, in an embodiment of the present application, heat treating the base glass includes: heating the base glass to 600-850°C at a rate of 1-20°C / min and keeping it warm for 1-3 hours; or, heating the base glass to 550-750°C at a rate of 1-20°C / min and keeping it warm for 0.5-4 hours to complete nucleation, and then heating the nucleated base glass to 650-900°C and keeping it warm for 0.5-3 hours to complete crystallization.

[0119] Exemplarily, the base glass is heated to 750° C. at a rate of 5° C. / min and kept at this temperature for 2 h.

[0120] Exemplarily, the base glass is heated to 800° C. at a rate of 5° C. / min and kept at that temperature for 2 h.

[0121] Exemplarily, the base glass is heated to 700° C. at a rate of 10° C. / min and kept at that temperature for 3 h.

[0122] Exemplarily, the base glass is heated to 650° C. at a rate of 5° C. / min and kept at this temperature for 3 h to complete nucleation, and then the nucleated base glass is heated to 800° C. and kept at this temperature for 0.5 h to complete crystallization.

[0123] Exemplarily, the base glass is heated to 700° C. at a rate of 3° C. / min and kept at this temperature for 2 hours to complete nucleation, and then the nucleated base glass is heated to 750° C. and kept at this temperature for 2 hours to complete crystallization.

[0124] It should be understood that the above heat treatment system is only used as an example and does not constitute a limitation of the present application. It should be understood that in actual operation, according to the base glass of different chemical components, the heat treatment system can be adjusted to obtain microcrystalline glass with different crystal phase types, crystal phase contents or crystal phase sizes. In this way, the transparency and mechanical properties of microcrystalline glass can be regulated.

[0125] It should be understood that during the crystallization process of the base glass in the embodiment of the present application, the chemical component P2O5 in the base glass can be used as a nucleating agent to effectively promote the formation of crystal nuclei and induce crystallization during the crystallization process. At the same time, due to the presence of the chemical component Nb2O5, the excessive growth or uneven growth of the phosphate crystal phase during the formation of the microcrystalline glass can be effectively suppressed. This is because at high temperatures, Nb2O5 and P2O5 compete for alkali metal oxides such as Na2O, K2O and Li2O, thereby satisfying the needs of each precipitating niobate or phosphate crystal phase. The higher the temperature, the stronger the competition of Nb2O5 for alkali metals, that is, it is easier to produce niobate crystal phases.

[0126] Therefore, in the embodiments of the present application, by controlling the amount of Nb2O5 introduced and the relative ratio of Nb2O5 to P2O5, the excessive growth or uneven growth of the phosphate crystal phase can be effectively controlled. Specifically, in the present application, the base glass is heat-treated to obtain a glass-ceramic including a nepheline crystal phase, a phosphate crystal phase, and a niobate crystal phase, wherein the formation of the niobate crystal phase inhibits the excessive growth or uneven growth of the phosphate crystal phase, thereby improving the mechanical properties of the glass-ceramic. Moreover, the niobate crystal phase in the glass-ceramic provided in the present application is a tiny crystal phase, the size of which is less than or equal to 80 nm, and its presence improves the mechanical properties of the glass-ceramic.

[0127] In conjunction with Table 2, the crystal phase composition, transparency and mechanical properties of Examples 1-16 in Table 1 and Comparative Example 1 after being treated under different heat treatment regimes are exemplified below.

[0128] Table 2:

[0129]

[0130] Table 2 (continued):

[0131]

[0132] As can be seen from Table 2, chemical composition and heat treatment system are two important factors affecting the transmittance and mechanical properties of microcrystalline glass.

[0133] First, from the perspective of chemical composition. As an example, the chemical composition in Comparative Example 1 does not include Nb2O5, and the microcrystalline glass made by microcrystallization of the base glass does not include a niobate crystal phase, such as Figure 5 As shown; and the microcrystalline glass is prone to cracking during cutting or cooling processes, while the microcrystalline glass obtained in Examples 6-8 under the same heat treatment system does not crack. This is because the phosphate crystals of the base glass of Comparative Example 1 grow excessively during heat treatment, such as Figure 6 As another example, under the same heat treatment system, the microcrystalline glass obtained in Examples 4 and 5 is opaque, while the microcrystalline glass obtained in Examples 6-8 is transparent. This is because the Nb2O5 content in Examples 4 and 5 is too high, resulting in no precipitation of phosphate crystal phase during the microcrystallization process, further making the final microcrystalline glass opaque.

[0134] Secondly, from the perspective of heat treatment system. As an example, Example 1 shows different mechanical properties (bursting or not bursting) under different heat treatments. Under the appropriate heat treatment system, microcrystalline glass with excellent performance can be obtained. For example, Example 1 is transparent when heat treated at 800℃ for 2h and does not burst when cut. Its microscopic morphology is as follows: Figure 7 As another example, Example 3 exhibits different light transmittances (transparent or semi-transparent) under different heat treatment regimes.

[0135] It should be understood that, in general, the chemical composition and the heat treatment system jointly affect the properties of the microcrystalline glass. For example, when the composition is Example 2, the microscopic morphology of the microcrystalline glass after heat treatment at 750°C for 2h is as follows: Figure 8 As shown, it can be seen that the crystal phase distribution and crystal phase size in this case are significantly better than the microscopic morphology presented by Example 1 when heat treated at 800°C for 2h. Therefore, in the actual preparation process of microcrystalline glass, the chemical composition and heat treatment system should be adjusted according to the actual situation, and this application will not go into details here.

[0136] Optionally, as a preferred method, on the basis of the above scheme, the base glass or the microcrystalline glass can be subjected to chemical strengthening treatment (ion exchange treatment) to further improve the mechanical properties of the microcrystalline glass.

[0137] In one implementation, after obtaining the microcrystalline glass, an ion exchange treatment may be performed on the microcrystalline glass to obtain a surface compressive stress layer, wherein the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

[0138] It should be understood that since the surface compressive stress layer is obtained through ion exchange treatment, the surface compressive stress layer also includes the crystal phases possessed by the microcrystalline glass itself, namely: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0139] Optionally, the ion exchange method can be a one-step method, i.e. exchanging sodium ions on the surface of the microcrystalline glass with potassium ions; or it can be a two-step method, i.e. first exchanging lithium ions in the surface of the microcrystalline glass with sodium ions, and then exchanging sodium ions in the surface of the microcrystalline glass with potassium ions.

[0140] The core process of this implementation method is: batch material preparation → glass melting → cooling and molding → microcrystallization → ion exchange treatment.

[0141] In this implementation, the preparation process of the microcrystalline glass also includes: performing ion exchange treatment on the microcrystalline glass so that the microcrystalline glass forms a surface compressive stress layer, so that it can withstand higher surface compressive stress and the mechanical properties are further improved.

[0142] In another implementation, the base glass may be subjected to ion exchange treatment before heat-treating the base glass, so that the microcrystalline glass obtained after the heat-treatment includes a surface compressive stress layer, and the surface compressive stress layer includes a hexagonal potassium pyroxene crystal phase.

[0143] It should also be understood that since the surface compressive stress layer is obtained through ion exchange treatment, the surface compressive stress layer also includes the crystal phases possessed by the microcrystalline glass itself, namely: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase.

[0144] Optionally, the ion exchange method can be a one-step method, i.e. exchanging sodium ions on the surface of the microcrystalline glass with potassium ions; or it can be a two-step method, i.e. first exchanging lithium ions in the surface of the microcrystalline glass with sodium ions, and then exchanging sodium ions in the surface of the microcrystalline glass with potassium ions.

[0145] The core process of this implementation method is: batch material preparation → glass melting → cooling and molding → ion exchange treatment → microcrystallization.

[0146] In this implementation, the base glass is subjected to ion exchange treatment so that the microcrystalline glass obtained after the base glass is heat treated includes a surface compressive stress layer, so that the microcrystalline glass can withstand higher surface compressive stress, thereby further improving the mechanical properties of the microcrystalline glass.

[0147] The present application provides a glass-ceramic product, wherein the glass-ceramic product is made of the glass-ceramic in any possible implementation manner described above. Optionally, the glass-ceramic product may be a housing in an electronic device or a glass cover plate above a display screen.

[0148] The microcrystalline glass products of the embodiments of the present application can be applied to devices with displays (or display products), for example, electronic devices (including mobile phones, tablets, computers, navigation systems, etc.); architectural products; transportation products (such as cars, trains, aircraft, ships, etc.), equipment products or any products that require a certain degree of transparency, scratch resistance, abrasion resistance or a combination of the above properties.

[0149] Fig. 9 is an exemplary structural diagram of an electronic device provided in an embodiment of the present application. As an example but not a limitation, Fig. 9 In the embodiment, the electronic device 900 is a mobile phone and includes a housing 910 and a display screen 920. The display screen 920 is mounted on the housing 910. The display screen 920 includes a glass cover plate 921 and a display module 922. The glass cover plate 921 is disposed on the display module 922. The housing 910 includes the microcrystalline glass in any of the embodiments described above; and / or the glass cover plate 921 includes the microcrystalline glass in any of the embodiments described above.

[0150] Optionally, the housing 910 may include a side surface and a rear surface, wherein the rear surface may also be referred to as a back plate. The glass cover may be referred to as a panel.

[0151] Optionally, the electronic device may further include electronic components (not shown) disposed inside the housing 910 , the electronic components including a circuit board, a processor, a camera, a flash, a microphone, a battery, etc., but not limited thereto.

[0152] Optionally, the display screen 920 may be a light emitting diode (LED) display screen, a liquid crystal display (LCD) display screen, or an organic light-emitting diode (OLED) display screen, but is not limited thereto.

[0153] Optionally, the glass cover plate 921 may be mounted on the display module 922 by means of colloid, or by other methods, which are not limited in the present application.

[0154] It should be understood that Fig. 9Just as an example, the electronic device of the embodiment of the present application can also be other electronic devices besides mobile phones, such as tablet computers, computers, navigation systems, etc. It should also be understood that the microcrystalline glass of the embodiment of the present application can be arranged on the front surface (panel) of the electronic device housing, or on the rear surface of the electronic device (for example, used as a battery back cover (back panel)) or side surface, etc.

[0155] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A glass-ceramic, characterized in that: include: Nepheline crystal phase, phosphate crystal phase, niobate crystal phase; the chemical components of the microcrystalline glass include Nb2O5 and P2O5; wherein, in terms of molar parts, the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

2. The glass-ceramic according to claim 1, characterized in that: In terms of molar parts, the chemical components of the microcrystalline glass include a first component, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts.

3. The glass-ceramic according to claim 2, characterized in that: The chemical composition of the microcrystalline glass also includes a second component, which includes at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

4. The glass-ceramic according to any one of claims 1 to 3, characterized in that: The microcrystalline glass includes a surface compressive stress layer, and the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

5. The glass-ceramic according to claim 4, characterized in that: The surface compressive stress of the surface compressive stress layer is greater than or equal to 200 MPa, and the depth of the surface compressive stress layer is greater than or equal to 15 μm.

6. The glass-ceramics according to claim 4 or 5, characterized in that: At least one of the nepheline crystal phase, the hexagonal potassium nepheline crystal phase, the phosphate crystal phase and the niobate crystal phase is a nanocrystalline phase, and a size of the nanocrystalline phase is less than or equal to 80 nm.

7. The glass-ceramic according to any one of claims 1 to 6, characterized in that: The light transmittance of the microcrystalline glass in the visible light spectrum range is greater than or equal to 75%.

8. The glass-ceramic according to any one of claims 1 to 7, characterized in that: The microcrystalline glass is colorless or light-colored and transparent.

9. The glass-ceramic according to any one of claims 1 to 8, characterized in that: The color coordinates of the microcrystalline glass in the CIE LAB color space are in the following ranges: L* is 80 to 100, a* is -20 to 5, and b* is -20 to 5.

10. A method for preparing glass-ceramics, characterized in that: include: preparing a substrate glass; The base glass is heat-treated to obtain microcrystalline glass, which includes: nepheline crystal phase, phosphate crystal phase, and niobate crystal phase; the chemical components of the microcrystalline glass include Nb2O5 and P2O5; wherein, in terms of molar parts, the proportion of Nb2O5 is 1 / 10 to 6 / 10 of the proportion of P2O5.

11. The preparation method according to claim 10, characterized in that: In terms of molar parts, the chemical composition of the matrix glass includes a first component, which includes: SiO2, 45 to 68 parts; Al2O3, 11 to 32 parts; P2O5, 1 to 8 parts; B2O3, 0 to 10 parts; Li2O, 0 to 15 parts; Na2O, 5 to 28 parts; K2O, 0 to 20 parts; Nb2O5, 0.5 to 4.8 parts; ZrO2, 0 to 3 parts; and Ta2O5, 0 to 3 parts.

12. The preparation method according to claim 11, characterized in that: The chemical composition of the matrix glass further includes a second component, which includes at least one of MgO, CaO, SrO, BaO and ZnO, and the proportion of the second component is 0.1 to 5 parts.

13. The preparation method according to any one of claims 10 to 12, characterized in that: The heat treatment of the substrate glass comprises: The base glass is heated to 600-850°C at a rate of 1-20°C / min and kept at this temperature for 1-3 hours; or, The base glass is heated to 550-750° C. at a rate of 1-20° C. / min and kept warm for 0.5-4 hours to complete nucleation, and then the nucleated base glass is heated to 650-900° C. and kept warm for 0.5-3 hours to complete crystallization.

14. The preparation method according to any one of claims 10 to 13, characterized in that: The method further comprises: The microcrystalline glass is subjected to ion exchange treatment to obtain a surface compressive stress layer, wherein the surface compressive stress layer includes a hexagonal kalcysite crystal phase.

15. The preparation method according to any one of claims 10 to 13, characterized in that: Before heat treating the base glass, the method further comprises: The base glass is subjected to ion exchange treatment, so that the microcrystalline glass obtained after the base glass is heat-treated includes a surface compressive stress layer, and the surface compressive stress layer includes a hexagonal kalcyrite crystal phase.

16. A glass-ceramic product, characterized in that: The microcrystalline glass product is made of the microcrystalline glass according to any one of claims 1 to 9.

17. An electronic device, characterized in that: The electronic device comprises a housing and a display screen, wherein the display screen is mounted on the housing, and the display screen comprises a glass cover plate and a display module, wherein the glass cover plate is arranged on the display module; Wherein, the shell comprises the microcrystalline glass according to any one of claims 1 to 9; and / or, The glass cover plate comprises the microcrystalline glass according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Opaque colored glass-ceramics comprising nepheline crystal phases

    US20150284288A1

  • Strong miserite glass-ceramics

    US6130178A